An introduction to patient-reported outcome measures (PROMs) in physiotherapy. Issue 2 (June 2015) - Kyte, D.G.; Calvert, M.; van der Wees, P.J.; ten Hove, R.; Tolan, S.; Hill, J.C.
Abstract: The use of patient-reported outcome measures (PROMs) is set to rise in physiotherapy. PROMs provide additional 'patient-centred' data which is unique in capturing the patient's own opinion on the impact of their disease or disorder, and its treatment, on their life. Thus, PROMs are increasingly used by clinicians to guide routine patient care, or for the purposes of audit, and are already firmly embedded in clinical research. This article seeks to summarise the key aspects of PROM use for physiotherapists, both in routine clinical practice and in the research setting, and highlights recent developments in the field. Generic and condition-specific PROMs are defined and examples of commonly used measures are provided. The selection of appropriate PROMs, and their effective use in the clinical and research settings is discussed. Finally, existing barriers to PROM use in practice are identified and recent physiotherapy PROM initiatives, led by the Royal Dutch Society for Physical Therapy are explored.